2018
DOI: 10.1016/j.cub.2018.04.063
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped Synaptic Connectivity Is Restored during Circuit Repair in the Adult Mammalian Retina

Abstract: Proper function of the central nervous system (CNS) depends on the specificity of synaptic connections between cells of various types. Cellular and molecular mechanisms responsible for the establishment and refinement of these connections during development are the subject of an active area of research [1-6]. However, it is unknown if the adult mammalian CNS can form new type-selective synapses following neural injury or disease. Here, we assess whether selective synaptic connections can be reestablished after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Cell–cell communications, such as synaptic connections, gap junctions, and exosomes, are fundamental to living organisms (Lloyd and McIntyre, 1955; Farquhar and Palade, 1965; Johnstone et al, 1987; Beier et al, 2018; Cervera et al, 2018; Stahl and Raposo, 2018). The tunneling nanotubes (TNTs), the fragile and inconspicuous membranous tunnel-like structures ranging 50 to 200 nm in diameter and 5 to 125 µm in length connecting two cells, have been reported in diverse cell types (Rustom et al, 2004; Gerdes et al, 2007; Hase et al, 2009; Lou et al, 2012; Gousset et al, 2013; Schiller et al, 2013; Austefjord et al, 2014; Burtey et al, 2015; Polak et al, 2015; Wang and Gerdes, 2015; Delage et al, 2016; Desir et al, 2016; Zhu et al, 2016; Keller et al, 2017; Vignais et al, 2017; Dupont et al, 2018; Panasiuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Cell–cell communications, such as synaptic connections, gap junctions, and exosomes, are fundamental to living organisms (Lloyd and McIntyre, 1955; Farquhar and Palade, 1965; Johnstone et al, 1987; Beier et al, 2018; Cervera et al, 2018; Stahl and Raposo, 2018). The tunneling nanotubes (TNTs), the fragile and inconspicuous membranous tunnel-like structures ranging 50 to 200 nm in diameter and 5 to 125 µm in length connecting two cells, have been reported in diverse cell types (Rustom et al, 2004; Gerdes et al, 2007; Hase et al, 2009; Lou et al, 2012; Gousset et al, 2013; Schiller et al, 2013; Austefjord et al, 2014; Burtey et al, 2015; Polak et al, 2015; Wang and Gerdes, 2015; Delage et al, 2016; Desir et al, 2016; Zhu et al, 2016; Keller et al, 2017; Vignais et al, 2017; Dupont et al, 2018; Panasiuk et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, recent evidence supports adaptive rather than solely destructive neural changes. For example, dendritic compensatory synapse formation occurs in retinal bipolar cells when various retinal cells, including rod and cone photoreceptors, have been ablated ( Beier et al, 2017 ; Beier et al, 2018 ; Care et al, 2019 ; Johnson et al, 2017 ; Shen et al, 2020 ). These studies suggested that rod or cone bipolar cell dendrites can extend their arbors and form new synapses with their correct targets (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Rewiring cone-cone bipolar cells or potentiating rod-rod bipolar cell signaling preserves light responses in photoreceptor-degenerating mice ( Leinonen et al., 2020 ; Shen et al., 2020 ). Bipolar cells also participate in compensatory dendritic remodeling and synapse formation in response to the loss of photoreceptors ( Beier et al., 2017 , 2018 ; Care et al., 2019 ; Johnson et al., 2017 ; Shen et al., 2020 ). Therefore, modulating retinal remodeling in response to photoreceptor loss may help maintain or improve retinal function in response to retinal degeneration.…”
Section: Discussionmentioning
confidence: 99%